Improving Children's Cognitive Development Using Image Media In Class B In IT Kindergarten Bunda RAhma Taratak Bukareh - Yeni Rahmawati; Zulmi Aryani; Nurhamidah Nst (Sean Institute, 2023)
The cognitive development of children in number recognition material is still slow, this is caused by the media used which is less creative and the methods used are not appropriate so that children quickly feel bored and no longer want to take part in learning. This can result in low cognitive development of children in number recognition material through image media. The type of this research is that PTK was carried out in group B IT Kindergarten Bunda Rahma Taratak Bukareh with 10 children. This research was conducted in 2 cycles with 2 meetings in each cycle. This research can be said to be successful if the success indicator reaches 75%. From analysis I cycle II, there has been an increase in children's cognitive development from each assessment indicator that the author carried out, so that in cycle II children's cognitive development has achieved more indicators of success, namely 75%, in each indicator the percentage of assessment of child development is already 90%, namely BSH 70% and BSB 20%. This means that the author has succeeded in improving children's cognitive development in number recognition material through image media in class B IT Kindergarten Bunda Rahma Taratak Bukareh